2011
DOI: 10.1007/s13197-011-0536-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on the microstructure of finger millet by X-ray diffraction and scanning electron microscopy

Abstract: Finger millet is one of the important minor cereals, and carbohydrates form its major chemical constituent. Recently, the millet is processed to prepare hydrothermally treated (HM), decorticated (DM), expanded (EM) and popped (PM) products. The present research aims to study the changes in the microstructure of carbohydrates using X-ray diffraction and scanning electron microscopy. Processing the millet brought in significant changes in the carbohydrates. The native millet exhibited A-type pattern of X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In the x-ray diffractogram, the sharp peaks are associated with the crystalline region while the diffused peaks with the amorphous region of the samples. [31] Corn starch (control) exhibited singlet and sharper peaks at 2θ values of 15 and 23º and a double or diffused peak at 2θ of 17 and 18º which is a characteristic of A-type crystallinity (Fig. 5).…”
Section: X-ray Diffractogramsmentioning
confidence: 98%
“…In the x-ray diffractogram, the sharp peaks are associated with the crystalline region while the diffused peaks with the amorphous region of the samples. [31] Corn starch (control) exhibited singlet and sharper peaks at 2θ values of 15 and 23º and a double or diffused peak at 2θ of 17 and 18º which is a characteristic of A-type crystallinity (Fig. 5).…”
Section: X-ray Diffractogramsmentioning
confidence: 98%
“…The crust has a structure normally found in the bulk of expanded snacks. Such an inhomogenous cell size distribution is obtained via preprocessing where the pellet contains a large air pocket in the middle of the pellet -acting as nucleation site for the large bubble (Dharmaraj et al, 2011). From a textural point of view such inhomogeneous structures are quite intriguing.…”
Section: Snack Structurementioning
confidence: 99%
“…Parboiling process involved steeping the grains for equilibrium moisture content, steaming or boiling to gelatinize the starch and finally dehydrating the grains to remove the moisture to a safe level appropriate for storage. Previous studies have shown an optimum steaming time of 30 min for finger millets (Dharmaraj et al 2011). In the present study two time periods (15 and 30 min) were used for the steaming of grains.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 93%
“…Parboiling is a popular hydrothermal tratment used for paddy to improve its milling yield and nutritional quality. However, limited published information is available for finger millet parboiling (Dharmaraj et al 2011;Bora et al 2018). The use of different processing methods may help improve the quality of FMP for rendering health benifits.…”
Section: Introductionmentioning
confidence: 99%